Second Trimester Abortion: A Dilation and Evacuation Simulation for Gynecologic Surgery and Obstetrics Residents - Kiley Hunkler; David Boedeker; Elizabeth Gill; Katelyn Simpkins; Katerina Shvartsman; Jill Brown; Sara Drayer (MedEdPORTAL)
Introduction The future of training in second trimester surgical abortions with dilation and evacuation (D&E) procedures faces ongoing legal and political scrutiny; thus, adjuncts to standard clinical experiences are exceedingly important. We sought to build medical trainees’ surgical familiarity with D&Es using a realistic simulation model. Methods The simulation began with an instructional video reviewing accessible and affordable materials used to build the fetal model (vaginal swabs, styrofoam ball, and putty) and the uterine model (collapsible water bottle). Required personnel roles included surgeon, surgical assistant, and facilitator. A standardized rubric was used to evaluate learners’ mastery of procedural learning objectives, and a pre- and postsimulation assessment measured learners’ knowledge and confidence before and after the activity. Consistency between iterations was maintained with use of standardized prompts and lectures. Total time for the activity, including setup and debrief, was 1 hour. Results Eighteen residents, medical students, and attendings participated in the simulation, and 100% completed the assessment. There was a demonstrated improvement in clinical knowledge of D&E steps (56% presimulation vs. 94% postsimulation, p < .001) and increased surgical confidence in performing D&Es after participating in the simulation (28% presimulation vs. 89% postsimulation, p < .001). The participants with prior clinical experience in performing D&Es rated the fetal, uterine, and cervical models as realistic components in the simulation. Discussion A gap now exists in access to clinical D&E training. This low-fidelity D&E simulation is a training tool that can fill this gap and improve learners’ familiarity with this surgical procedure.